CRH receptor antagonism reverses the effect of social subordination upon central GABAA receptor binding in estradiol-treated ovariectomized female rhesus monkeys - Michopoulos, V.; Embree, M.; Reding, K.; Sanchez, M.M.; Toufexis, D.; Votaw, J.R.; Voll, R.J.; Goodman, M.M.; Rivier, J.; Wilson, M.E.; Berga, S.L. (Neuroscience, 2013)
•Social subordination alters GABAARs binding in estradiol-treated female monkeys.•Status effect on GABAAR is site specific, only seen in the prefrontal cortex.•CRH receptor antagonism reverses status differences in GABAAR binding.•Implicates the stress axis in the dysregulation of GABAAR in subordinate females.•Provides mechanism by which subordination alters the actions of estradiol. Persistent exposure to environmental stressors causes dysregulation of the limbic–hypothalamic–pituitary–adrenal (LHPA) axis and alters GABAA receptor (GABAAR) levels throughout the brain. Social subordination in socially housed female rhesus results in distinctive stress-related physiological and behavioral phenotypes that are dependent on the ovarian hormone estradiol (E2). In the present study, we utilized ovariectomized adult female rhesus monkeys undergoing hormone replacement with E2 to test the hypothesis that the chronic psychosocial stress of subordination alters GABAAR binding potential (GABAAR BPND) in limbic regions implicated in emotional processing including the prefrontal cortex, temporal lobe (amygdala and hippocampus), and hypothalamus. Furthermore, we tested the hypothesis that peripheral administration of a corticotropin-releasing hormone (CRH) receptor antagonist (astressin B) would reverse the alterations in GABAAR binding within these regions in subordinate females. After subjects received astressin B or saline for three consecutive days, GABAAR BPND was determined by positron emission tomography (PET) using 18F-flumazenil as a radioligand. T1-weighted structural magnetic resonance imaging scans were also acquired for PET scan co-registration, in order to perform a region of interest analysis using the pons as a reference region. Compared to socially dominant females, subordinate females exhibited increased GABAAR BPND in the prefrontal cortex but not in the temporal lobe or the hypothalamus. Administration of astressin B eliminated the status difference in GABAAR BPND in the prefrontal cortex, suggesting that the chronic stressor of social subordination modulates GABAergic tone via effects on CRH and the LHPA axis, at least in prefrontal regions.